Perspectives of gamification in teaching from the aspect of cybernetic-information theory - Tasić, Nemanja; Kovačević, Miodrag (Norma, 2024)
Gamification has become an increasingly popular approach to improve student engagement and motivation in the classroom. Gamification implies a way of introducing activities that contribute to the development of logic and lead to a greater degree of fun for students during classes. Cybernetic-information theory, which emphasizes feedback, adaptation, and communication in complex systems, provides a framework for understanding the potential benefits and challenges of gamification in education. The aim of the paper is to show that gamification, when designed appropriately, can be a useful tool for increasing student engagement and motivation, and that it is in line with the principles of cybernetic-information theory. The results of the paper indicate that students not only learn in a fun environment, but are able to improve their creativity and problem solving while learning subconsciously. Further research is needed to investigate the effectiveness of gamification in teaching and to identify best practices for designing gamified learning activities.